2019
DOI: 10.1002/ange.201903898
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Conductivity at the Single‐Molecule Scale

Abstract: In most junctions built by wiring as ingle molecule between two electrodes,the electrons flow along only one axis: between the two anchoring groups.However,molecules can be anisotropic,a nd an orientation-dependent conductance is expected. Here,w ef abricated single-molecule junctions by using the electrode potential to control the molecular orientation and access individual elements of the conductivity tensor. We measured the conductance in two directions,a long the molecular plane as the benzener ing bridges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…One well- studied ACA is trimesic acid (TMA, 1,3,5-benzenetricarboxylic acid). 7,9,11,26−34 It was reported that TMA can form long-range ordered hexagonal (honeycomb) and other shaped structures on different substrates such as Au(111), 11,26,35 HOPG, 29,36 and Cu(100) 34 in the electrolyte 26 as well as in air and/or organic solvents. 29 When the number of carboxyl groups is reduced to two, three possible structures for benzenedicarboxylic acids are possible depending on the relative positions of the carboxylic acid (−COOH) groups, i.e., 1,2-benzenedicarboxylic acid (phthalic acid, PA), 1,3-benzenedicarboxylic acid (isophthalic acid, IA), and 1,4-benzenedicarboxylic acid (terephthalic acid, TPA).…”
Section: ■ Introductionmentioning
confidence: 99%
“…One well- studied ACA is trimesic acid (TMA, 1,3,5-benzenetricarboxylic acid). 7,9,11,26−34 It was reported that TMA can form long-range ordered hexagonal (honeycomb) and other shaped structures on different substrates such as Au(111), 11,26,35 HOPG, 29,36 and Cu(100) 34 in the electrolyte 26 as well as in air and/or organic solvents. 29 When the number of carboxyl groups is reduced to two, three possible structures for benzenedicarboxylic acids are possible depending on the relative positions of the carboxylic acid (−COOH) groups, i.e., 1,2-benzenedicarboxylic acid (phthalic acid, PA), 1,3-benzenedicarboxylic acid (isophthalic acid, IA), and 1,4-benzenedicarboxylic acid (terephthalic acid, TPA).…”
Section: ■ Introductionmentioning
confidence: 99%
“…24 STM images of ordered molecular structures before and after the break junction procedure (reported in our previous studies) show the formation of local holes/islands with the size of one or a few molecules while the surrounding ordered molecular network remained intact. 22,23 The junction formation is a gentle and soft process (the tip moves toward the surface in 0.1 nm steps until it touches the surface and does not go far beyond the initial contact). 22,23 High resolution STM images taken after break junction measurements with the same tip strongly indicate that the tip does not undergo a destructive crashing and deformation during break junction formation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Materials having an anisotropic crystal structure often exhibit anisotropy in the electrical conductivity. [1][2][3][4][5][6][7][8][9] Since there are wide varieties of crystal structures in complex transition metal oxides (TMOs), many complex TMOs exhibit anisotropy in the electrical conductivity as summarized in Table S1. [10][11][12][13][14][15] For example, the electrical conductivity of hollandite BaRu6O12 along double chain of edged sharing RuO6 is ~6 times larger than the perpendicular direction at 300K.…”
Section: Introductionmentioning
confidence: 99%